Mechanisms of Cervical Spine Injuries for Non-Fatal Motorcycle Road Crash - Ooi, Soo Shen; Wong, Shaw Voon; Radin Sohadi, Radin Umar; Abdul Aziz, Azhar; Yeap, J. S.; Megat Ahmad, Megat Mohamad Hamdan (2004)
Survival spine injuries such as subluxation and fracture dislocation have long been known to result in severe consequences, as well as the trauma management itself. The injury to the region to the region has been identified as one of the major causes of death in Malaysian motorcycle involved in road crashes, besides head and chest injuries (Pang, 1999). Despite this, cervical spine injury in motorcyclists it not a well-studied injury, unlike the whiplash injury in motorcar incidents. The present study is a retrospective study of the mechanism of injury in cervical spine sustained by Malaysian motorcyclists, who were involved in road crash using an established mechanistic classification system. This will serve as an initial step to look at the cervical injuries pattern, the information obtained gives engineer ideas to facilities design and safety features to reduce injuries. All cervical spine injured motorcyclists admitted to Hospital Kuala Lumpur between January 1, 2000 and December 31, 2001 were included in the present study. Based on the medical notes and radiological investigations (X-rays, CT and MRI scans), the mechanisms of injuries were formulated using the injury mechanisms classification. The result shows that flexion of the cervical vertebrae is the most common vertebral kinematics in causing injury to motorcyclists. This indicates that the cervical vertebrae sustained a high-energy loading at flexion movement in road crash, and exceeded its tolerance level. This high frequency of injury at the C5 vertebra and C5-C6 intervertebral space are recorded. Classification based on the Abbreviated Scale (AIS) is made to give a view on injury severity, 9.1% of the study samples have been classified as AIS code 1, 51.5% with AIS and 21.2% with AIS.